Characterization of the unfolded state of bovine alpha-lactalbumin and comparison with unfolded states of homologous proteins. - Wirmer, J; Berk, H; Ugolini, R; Redfield, C; Schwalbe, H (2006)
The unfolded states of three homologous proteins with a very similar fold have been investigated by heteronuclear NMR spectroscopy. Secondary structure propensities as derived from interpretation of chemical shifts and motional restrictions as evidenced by heteronuclear (15)N relaxation rates have been analyzed in the reduced unfolded states of hen lysozyme and the calcium-binding proteins bovine alpha-lactalbumin and human alpha-lactalbumin. For all three proteins, significant deviations from random-coil predictions can be identified; in addition, the unfolded states also differ from each other, despite the fact that they possess very similar structures in their native states. Deviations from random-coil motional properties are observed in the alpha- and the beta-domain in bovine alpha-lactalbumin and lysozyme, while only regions within the alpha-domain deviate in human alpha-lactalbumin. The motional restrictions and residual secondary structure are determined both by the amino acid sequence of the protein and by residual long-range interactions. Even a conservative single point mutation from I to L in a highly conserved region between the two alpha-lactalbumins results in considerable differences in the motional properties. Given the differences in oxidative folding between hen lysozyme and alpha-lactalbumin, the results obtained on the unfolded states suggest that residual long-range interactions, i.e., those between the alpha- and the beta-domain of lysozyme, may act as nucleation sites for protein folding, while this property of residual structure is replaced by the calcium-binding site between the domains in alpha-lactalbumin.